Immunity for Humanity: A Revolutionary Endeavour towards Holistic Health Living: Exploring the Impact of Immunity on Human Health (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Immunity is the human body's ability to resist toxins or organisms that cause damage to the tissues and organs, thereby demonstrating a defence mechanism for an improved quality of life. (Guyton and hall 2011)